2019
DOI: 10.18502/avr.v28i3.1229
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive-behavioral training and muscle relaxation on the degree of tinnitus and the quality of sleep

Abstract: Background and Aim: Tinnitus is an annoying distressing phantom phenomenon that can cause major problems, such as insomnia and sleep deprivation. Therefore, the present study was conducted to determine the effects of cognitive-behavioral training (CBT) and muscle relaxation on the level of tinnitus and the quality of sleep in patients with tinnitus in Ahvaz City in 2018−2019. Methods: This study is a semi-experimental, pretest, post-test, and follow-up with control group. There are two experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… Biesinger et al (2010) reported Qigong, a mindful exercise and active relaxation, reduced tinnitus severity. Small scale studies comparing CBT and relaxation have found variable results, and for example, Davies et al (1995) were unable to conclude the efficacy of relaxation, whereas Tavakoli et al (2019) reported both treatments effective in reducing tinnitus distress. The efficacy of ICBT for tinnitus has generally be compared with other therapies such as ACT ( Hesser et al, 2012 ), usual care ( Beukes et al, 2018b ), but not specifically with applied relaxation in isolation.…”
Section: Introductionmentioning
confidence: 99%
“… Biesinger et al (2010) reported Qigong, a mindful exercise and active relaxation, reduced tinnitus severity. Small scale studies comparing CBT and relaxation have found variable results, and for example, Davies et al (1995) were unable to conclude the efficacy of relaxation, whereas Tavakoli et al (2019) reported both treatments effective in reducing tinnitus distress. The efficacy of ICBT for tinnitus has generally be compared with other therapies such as ACT ( Hesser et al, 2012 ), usual care ( Beukes et al, 2018b ), but not specifically with applied relaxation in isolation.…”
Section: Introductionmentioning
confidence: 99%